2014
DOI: 10.1002/jssc.201301350
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of quinolones in cosmetic products by ultra high performance liquid chromatography with tandem mass spectrometry

Abstract: This study developed an improved analytical method for the simultaneous quantification of 13 quinolones in cosmetics by ultra high performance liquid chromatography combined with ESI triple quadrupole MS/MS under the multiple reaction monitoring mode. The analytes were extracted and purified by using an SPE cartridge. The limits of quantification ranged from 0.03 to 3.02 μg/kg. The precision for determining the quinolones was <19.39%. The proposed method was successfully developed for the determination of quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Many types of commercially available SPE columns have been employed to extract the allowed and prohibited substances in cosmetics. Coumarin derivatives and quinolones were extracted using Oasis HLB , n ‐nitrosodiethanolamines were extracted with Bond Elut Accu CAT , hexapeptides were extracted using HILIC , dexpanthenols were extracted by Adsorbex NH 2 , fullerenes were extracted using Strata C‐18 E , and semipermanent dyes were extracted with Strata‐X cartridges . The results demonstrated that the proposed procedures can obtain high extraction efficiency.…”
Section: Sample Preparation Techniquesmentioning
confidence: 99%
“…Many types of commercially available SPE columns have been employed to extract the allowed and prohibited substances in cosmetics. Coumarin derivatives and quinolones were extracted using Oasis HLB , n ‐nitrosodiethanolamines were extracted with Bond Elut Accu CAT , hexapeptides were extracted using HILIC , dexpanthenols were extracted by Adsorbex NH 2 , fullerenes were extracted using Strata C‐18 E , and semipermanent dyes were extracted with Strata‐X cartridges . The results demonstrated that the proposed procedures can obtain high extraction efficiency.…”
Section: Sample Preparation Techniquesmentioning
confidence: 99%
“…For cosmetic products, illicit substances are also added to enhance short-term cosmetic effectiveness. Common banned additives include antibiotics [10, 11], corticosteroids [1215], sexual hormones (oestrogens [16], progestogens [16], androgen [17]), pharmacologically active substances [1618], prohibited preservatives (parabens [1922], methyldibromoglutaronitrile [23]), whitening agents [13, 24], phthalates [2528], and nitromusk fragrances [25, 28]. Long-term exposure to these substances could cause adverse effects such as skin irritation, allergic reactions, and antibiotic resistance, which represents a severe risk to public health.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical techniques that have been reported for the chemical analysis of foods and cosmetic products include thin layer chromatography [29, 30], capillary electrophoresis [22, 31], gas chromatography (GC) with flame ionization detection [21, 32] or coupled with various types of mass spectrometers [19, 20, 23, 25, 26, 28, 3336], high-performance liquid chromatography (HPLC) using ultraviolet [10, 12, 16, 17, 24, 37], electrochemical detection [38] or coupled with various types of mass spectrometers [1, 1117, 26, 35, 39]. These methods are typically implemented in analytical laboratories and performed by experienced chemists using bench-top equipment.…”
Section: Introductionmentioning
confidence: 99%
“…To date modern UHPLC–MS/MS equipment is used for precise and accurate analyte determination, which has following advantages: higher level of selectivity and sensitivity, applicability for fast qualitative screening and for precise quantitative analysis . We have determined a variety of chemical residues, such as carbamates, mycotoxins, and antibiotics by UHPLC–MS/MS in our previous studies . In this study, several plant growth regulators and fungicides in fruits were analyzed.…”
Section: Introductionmentioning
confidence: 99%